Environmental and Behavioral Determinants of Leptospirosis in an Endemic Tropical Region: A Case-Control Study in Indonesia - Prihayati; Ari Widodo; Ismarina; Titin Nasiatin; Istiana (KHD Production, 2026)
Leptospirosis remains an escalating public health challenge in tropical endemic regions, necessitating a deeper understanding of its localized transmission dynamics. This study aimed to identify the specific individual and environmental risk factors significantly associated with leptospirosis incidence in Serang Regency, Indonesia. A quantitative case-control study was conducted involving 62 respondents, comprising 31 confirmed cases and 31 matched controls. Data were analyzed using bivariate Chi-square tests and multivariate logistic regression to determine significant associations and calculate precise odds ratios (OR) with 95% confidence intervals. Multivariate analysis revealed that the non-use of personal protective equipment (PPE) was the most dominant risk factor (p=0.026; OR=10.435), followed by poor handwashing habits (p=0.017; OR=4.444), inadequate house gutter conditions (p=0.032; OR=3.906), the presence of rat footprints (p=0.040; OR=3.385), and residing in flood-prone areas (p=0.040; OR=3.385). Conversely, the conditions of household clean water facilities and trash bins demonstrated no statistically significant association with disease incidence in this cohort. A synergistic interplay of micro-environmental hazards and modifiable behavioral deficits drives leptospirosis transmission in this region. Public health interventions must urgently prioritize targeted PPE distribution, rigorous peri-domestic rodent control, and community-level hygiene education to mitigate future outbreak risks effectively.